Influence of venturi cone angles on jet aeration systems - Baylar, A; Ozkan, F; Ozturk, M (Thomas Telford Publishing, 2005)
Aeration involves the intimate mixing of air with water. Air contains 21% oxygen and thus aeration adds dissolved oxygen that is vital to the sustained health of ponds and lakes, reversing lake degradation. Water jet aeration is an effective method of achieving this. A water jet passing through the surrounding air entrains a substantial amount of air bubbles into the receiving water and creates a large air-water contact area. This paper investigates the addition of a venturi tube in a plunging water jet aeration system and, in particular, the effect of varying angles of converging and diverging cones and outlet lengths on air entrainment. A negative pressure draws air in through holes at the throat portion of the venturi tube. The resulting aeration of the jet affects its expansion and its surface roughness and hence the air entrainment rate. It was demonstrated that the values of the air entrainment rate of the venturi tube were significantly higher than those for a circular nozzle. As a result, venturi tubes can be used as highly effective aerators in aeration systems.
Keywords: hydraulics & hydrodynamics; pipes & pipelines; research & development